Neuromuscular spine deformity - Samdani, Amer F.; Newton, Peter O.; Sponseller, Paul D.; Shufflebarger, Harry L.; Betz, Randal R. (Thieme, 2018)
"About 85% of spine deformities (scoliosis, kyphosis, lordosis) are idiopathic, but some forms are caused by severe neuromuscular disorder such as muscular dystrophy, cerebral palsy, Friedreich's ataxia, and spinal cord tumors and lesions. These are more difficult conditions, since curve progression is much greater than in idiopathic conditions and bracing does not usually prevent progression of the spinal curvature. Smaller curvatures in nonambulatory patients can sometimes be treated by wheelchair modifications, but most patients will undergo surgery. These surgeries are complex because of the severity of the condition itself and because of the various other medical conditions affecting these patients. There is currently no book on the topic, and chapters in spine deformity books give the topic scant coverage. Samdani et al are the world's leader in this field, and they will present the definitive book on the topic, featuring foundational chapters, coverage of the specific neuromuscular disorders, surgical techniques, and postop considerations and complications, and the will be accompanied by surgical videos. The Authors are members of the prestigious Harms Study Group, a worldwide association of spine surgeons performing multi-center research studies on scoliosis"--Provided by publisher